Thimerosal induces skin pseudo-allergic reaction via Mas-related G-protein coupled receptor B2. Issue 3 (September 2019) - Peng, Bin; Che, Delu; Hao, Yong; Zheng, Yi; Liu, Rui; Qian, Ye; Cao, Jiao; Wang, Jue; Zhang, Yongjing; He, Langchong; Geng, Songmei
Highlights: A novel pseudo-allergic mouse model was developed. Thimerosal may cause contact dermatitis through the mechanism of pseudo-allergic reaction. MrgprB2-mediated mast cell activation contributes to pseudo-allergic reaction induced by thimerosal in mice. Pseudo-allergic reaction induced by thimerosal may be a possible explanation for its clinical irrelevance. Abstract: Background: Thimerosal has been used as a preservative in many products which may cause contact dermatitis. It is the second most common allergen in positive patch test reactions, though being a clinical irrelevant allergen. Thimerosal-induced contact dermatitis is generally considered to be a delayed-type hypersensitivity reaction, but it is difficult to explain the fact that most patients develop an allergic reaction upon first encounter with thimerosal. Recent studies have demonstrated the association between Mas-related G protein coupled receptor X2 (MRGPRX2) and pseudo-allergic reactions which occur at the first contact with stimulation. This suggests the possibility that thimerosal may cause contact dermatitis via MRGPRX2 mediated mechanism. Objectives: To investigate the role of Mas-related G-protein coupled receptor B2 (MrgprB2)/MRGPRX2 in contact dermatitis induced by thimerosal. Methods: Thimerosal induced pseudo-allergic reactions via MrgprB2/ MRGPRX2 were investigated using a novel skin pseudo-allergic reaction mouse model, footpad swelling and extravasation assays in vivo and mast cell degranulation assay in vitro . Results: Thimerosal induced contact dermatitis in dorsal skin and footpad swelling in wild-type mice, but had no significant effect in MrgprB2-knockout mice. Thimerosal-induced dermatitis is characterized by infiltration of inflammatory cells and elevation of serum histamine and inflammatory cytokines, rather than elevation of serum IgE level. Thimerosal increased the intracellular Ca 2+ concentration in HEK293 cells overexpressing MrgprB2/MRGPRX2. Downregulation of MRGPRX2 resulted in the reduced degranulation of LAD2 human mast cells. Conclusions: MrgprB2 mediates thimerosal-induced mast cell degranulation and pseudo-allergic reaction in mice. MRGPRX2 may be a key contributor to human contact dermatitis.